Acoustic analysis and dataset of transitions between coupled rooms - McKenzie, Thomas; Schlecht, Sebastian J.; Pulkki, Ville (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2021)
The measurement of room acoustics plays a wide role in audio research, from physical acoustics modelling and virtual reality applications to speech enhancement. While vast literature exists on position-dependent room acoustics and coupling of rooms, little has explored the transition from one room to its neighbour. This paper presents the measurement and analysis of a dataset of spatial room impulse responses for the transition between four coupled room pairs. Each transition consists of 101 impulse responses recorded using a fourth-order spherical microphone array in 5 cm intervals, both with and without a continuous line-of-sight between the source and microphone. A numerical analysis of the room transitions is then presented, including direct-to-reverberant ratio and direction of arrival estimations, along with potential applications and uses of the dataset.
CRIS-Team Scopus Importer:2023-11-06
Keywords: Acoustic Measurement; Coupled Rooms; Room Impulse Response; Room Transition